Using metamemory measures and memory tests to estimate eyewitness free recall performance. Issue 1 (2nd January 2020) - Saraiva, Renan Benigno; Hope, Lorraine; Horselenberg, Robert; Ost, James; Sauer, James D.; van Koppen, Peter J.
ABSTRACT: Using a mock witness methodology, we investigated the predictive value of metamemory measures and objective memory tests as indicators of eyewitness free recall performance. Participants ( n = 208) first completed a metamemory assessment that included assessments of self-rated memory capacity, memory development and use of strategies. In a separate session, participants watched a mock-crime video and provided a free recall account, followed by one out of four independent memory tests (i.e., free recall, cued recall, face recognition and general knowledge). Accuracy, amount of details reported, confidence and over/underconfidence in the eyewitness free recall were the main dependent variables. Results indicated three main findings: (1) subjective assessments of memory capacity were not related to eyewitness free recall performance; (2) although individual confidence and over/underconfidence was somewhat stable across different memory tests, accuracy was less stable; and (3) individuals with higher self-rated memory capacity had a slightly stronger confidence-accuracy relation in free recall. These results are discussed with respect to metamemory assessments and performance stability across memory tests of different domains.